Assembling a desktop robotic arm based hydrogel extrusion system - Khadijah Mohamed Hussain (2018)
Three-Dimensional (3D) bioprinters have been a technological breakthrough in biomedical applications, specifically in tissue engineering. In hopes of increasing the range of motion of these bioprinters in order to construct functional 3D bioprinted structures spatially without any pre-fabricated scaffolds on more complex surfaces, an evaluation was done to find out the capabilities of integrating a desktop six axis robotic arm into the system. This robotic arm 3D bioprinter is aimed to be able to perform minimally-invasive operations for the restoration and transplantation of essential organs done by surgeons straight onto a living wounded body. To be able to achieve that performance, the robotic arm 3D bioprinter requires a high level of steadiness for its printing units, movement repeatability and uniform construct fabrication of biomaterials which are of micro-dimensions. This high levels of precision in nano- and microfabrications can only be replicated by machines, in this case, a robotic arm which has the flexibility in movements like a human arm, an unmatched capability of a human. Thus, a six axis robotic arm was built with fully operational bipolar stepper motors, and several tests were done to evaluate its potential in performing high precision movements.